2016
DOI: 10.1589/jpts.28.807
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increasing maximal aerobic exercise on serum gonadal hormones and alpha-fetoprotein in the luteal phase of professional female soccer players

Abstract: [Purpose] The performance of female athletes during their menstrual period has attracted the attention of researchers for many years. It is known that the menstrual period changes with exercise. Alpha-fetoprotein (AFP) is an oncofetal protein. In this study, the effect of maximal aerobic exercise in the luteal phase on some hormones and AFP in female athletes was researched. [Subjects and Methods] Twelve volunteers and healthy female footballers with normal menstrual cycles volunteered for this study as subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…A more significant increase was seen in females during the early follicular to pre-ovulatory phase in response to HIIE as compared to males. Otağ et al, (2016), found an increase in the level of estradiol and a decreased level of FSH during the luteal phase in female soccer players in response to an acute maximal aerobic exercise, which was in accordance with our findings. It shows that, independent of the phase of the menstrual cycle, the HIIE response of estradiol and FSH is similar to that of acute maximal aerobic exercise in healthy young females.…”
Section: Female Gonadal Hormones (Estradiol Lh Fsh)supporting
confidence: 92%
See 1 more Smart Citation
“…A more significant increase was seen in females during the early follicular to pre-ovulatory phase in response to HIIE as compared to males. Otağ et al, (2016), found an increase in the level of estradiol and a decreased level of FSH during the luteal phase in female soccer players in response to an acute maximal aerobic exercise, which was in accordance with our findings. It shows that, independent of the phase of the menstrual cycle, the HIIE response of estradiol and FSH is similar to that of acute maximal aerobic exercise in healthy young females.…”
Section: Female Gonadal Hormones (Estradiol Lh Fsh)supporting
confidence: 92%
“…Serum VEGF increase in response to HIIE, was observed in our study (2.73% rise in males and 0.06% rise in females), which was not statistically significant (Figure 2G). Sex hormones influence serum levels of VEGF (Berciano Guerrero et al, 2010) and acute exercise affects the levels of these sex hormones (Monje et al, 2020;Otağ et al, 2016).…”
Section: Vegfmentioning
confidence: 99%
“…Some studies have focused on the exercise response to ovarian hormones ( Bonen et al, 1981 ; Jurkowski et al, 1978 ). A recent study shows that LH and FSH were significantly increased immediately after exercise particularly starting with running (8 km/h) increasing 0.5 km/h per minute, instead, progesterone activity decreased significantly ( Otağ et al, 2016 ). Progesterone is a hormone detectable in saliva as well as other hormones like cortisol, androgens (including testosterone and dehydroepiandrosterone), estrogen, and aldosterone.…”
Section: Introductionmentioning
confidence: 99%